Los incidentes de rebaja y aumento de pensión alimenticia y el derecho de igualdad. - Salazar Altamirano, Andrés Gonzalo (2023)
This research shows the results on the incidents of reduction and increase of alimony and the right of equality, since currently there is a controversy between the correct application of this principle for the benefit of the provider, for this the purpose of the research was to analyze the incidents of reduction and increase of alimony today in relation to the right of equality for the benefit of the provider. The methodology applied a descriptive type of research, with a cross-sectional quantitative approach, which accompanied by a data collection technique based on a survey consisting of 8 closed questions that allowed the development of the dimensions of the study variables. The target population was the applicants with cases in the Riobamba canton from January until June 2023, considering the data obtained from the unit of Jurimetric Studies and Judicial Statistics, obtaining a sample of 101 people. Among the main results was possible to identify that there is a violation of the principle of equality in benefit of the feeders, since the welfare of the minor is prevailing. In addition, it identified that the main cause for the increase or reduction of the alimony the variation of the income of the breadwinner.